Mitigation Strategy of Disaster Based on Information Technology in Semarang City - Rizky Muliani Dwi Ujianti; Mega Novita; Iffah Muflihati (Indonesian Journal on Geoscience, 2023)
Semarang is a city located on the northern coast of the Java Sea which makes it becomes one of the cities threatened by tidal flooding. Besides tidal flood inundation, several other disasters occuring in Semarang include fires, fallen trees, floods, landslides, hurricanes, and collapsed houses. This study identified the disasters occurred in Semarang City from 2012 through 2021, as well as the strategies to cope with them in general, and specifically using information technology, namely Geographic Information System (GIS) maps. The data in this study were obtained from Regional Development Planning Board, Public Works Office, Central Bureau of Statistics (BPS), Semarang City Social Service, and several related stakeholders. Those data were, then, visualized on a GIS map. The findings indicated that one method of mitigation is the use of GIS maps of floods and landslides, as well as disaster mitigation through Semarang economy and government policies Keywords: Semarang, GIS, tidal, flooding, disaster, mitigation